Investigation of the Electrodialysis of Sodium Tungstate Solutions for the Production of Tungstic Acid - Adelya Dauletbakova; Bolotpay Baimbetov; Yeleussiz Tazhiyev; Gulnara Moldabayeva (Applied Sciences, 2025)
Industrial technologies for processing tungsten concentrates using soda roasting or autoclave leaching are based on the production of alkaline sodium tungstate solutions that contain impurities such as silicon, phosphorus, arsenic, and others. The purification of these solutions from impurities requires the neutralization of excess soda or alkali with inorganic acids, which leads to the formation of chloride and sulfate effluents that are subsequently discharged into waste repositories. An analysis was carried out on existing methods for the production and processing of sodium tungstate solutions using HNO3 and NH3, as well as extraction and sorption techniques involving anion exchange resins. Currently, processes such as nanofiltration, reverse osmosis, and electrodialysis are being applied for water purification and the treatment of sulfate and chloride effluents. These processes employ various types of industrially manufactured membranes. For the purpose of electrodialysis, a two-compartment electrodialyzer setup was employed using cation-exchange membranes of the MK-40 (Russia) and EDC1R (China) types. The composition and structure of sodium tungstate, used as the starting reagents, were analyzed. Based on experiments conducted on a laboratory-scale unit with continuous circulation of the catholyte and anolyte, dependencies of various parameters on current density and process duration were established. Stepwise changes in the anolyte pH were recorded, indirectly confirming changes in the composition of the Na2WO4 solution, including the formation of polytungstates of variable composition and the production of H2WO4 via electrodialysis at pH < 2. The resulting tungstic acid solutions were also analyzed. The conducted studies on the processing of sodium tungstate solutions using electrodialysis made it possible to obtain alkaline solutions and tungstic acid at a current density of 500–1500 A/m2, without the use of acid for neutralization. Yellow tungstic acid was obtained from the tungstic acid solution by evaporation.